THE ENLIGHTENMENT – THE PAST (HISTORY) OR THE PRESENT (HERE AND NOW) - Valentina Mironska-Hristovska (Philological Studies, 2019)
This is a comparative literature study of the aftermath of the Enlightenment and its impact on the current present, specifically in the context of Europe and the Balkans. The study includes an evolutionary analysis of the cultural, economic, political and nationalist effects of the Enlightenment and their reflections in modern world globalized society. At the same time, the study covers the agents of the Enlightenment on the Balkans and the consequences of their endeavors, as well as historic events and the emergence of nationalism in the 19th century as the reason for the change of the visionary mission of the leaders of the movement, evidenced by Michel Foucault’s famous statement: “I do not know whether we will ever reach mature adulthood. Many things in our experience convince us that the historical event of the Enlightenment did not make us mature adults, and we have not reached that stage yet”.